A Study on 21st Century Skills Integration in the English Textbook for Senior High School: Kajian Integrasi Keterampilan Abad 21 dalam Buku Teks Bahasa Inggris untuk Sekolah Menengah Atas - Rakhmawati, Ditta Mustika; Priyana, Joko (Universitas Muhammadiyah Sidoarjo, 2019)
To help students successful in global future, 21stcentury skills have become important aspects to enable them to function appropriately and effectively within a global community of English language speakers. Students have to be facilitated with learning materials that are suitable with this demand. This study aims to reveal the 21stcentury skills that are integrated in the English textbook and to find out how those skills are integrated. The data were gathered using checklists and analyzed by calculating the number of occurrences of each skill of 21stcentury and identifying the strategies used in its integration. The results showed that there are 11 skills integrated in the textbook namely critical thinking and problem solving, communication, collaboration, creativity and innovation, information and communication technology (ICT), media literacy, leadership and responsibility, productivity and accountability, social and cross-cultural, initiative and self-direction, and flexibility and adaptability. Those skills are integrated through Nunan’s task components namely goals, inputs, procedures, teacher roles, learner roles, settings, and other strategies including notes, quotes, and points to ponder.